Development of diagnostic criteria and a prognostic score for hepatitis B virus-related acute-on-chronic liver failure. Issue 12 (19th September 2017) - Wu, Tianzhou; Li, Jiang; Shao, Li; Xin, Jiaojiao; Jiang, Longyan; Zhou, Qian; Shi, Dongyan; Jiang, Jing; Sun, Suwan; Jin, Linfeng; Ye, Ping; Yang, Lingling; et al.
Abstract : Objective: The definition of acute-on-chronic liver failure (ACLF) based on cirrhosis, irrespective of aetiology, remains controversial. This study aimed to clarify the clinicopathological characteristics of patients with hepatitis B virus-related ACLF (HBV-ACLF) in a prospective study and develop new diagnostic criteria and a prognostic score for such patients. Design: The clinical data from 1322 hospitalised patients with acute decompensation of cirrhosis or severe liver injury due to chronic hepatitis B (CHB) at 13 liver centres in China were used to develop new diagnostic and prognostic criteria. Results: Of the patients assessed using the Chronic Liver Failure Consortium criteria with the exception of cirrhosis, 391 patients with ACLF were identified: 92 with non-cirrhotic HBV-ACLF, 271 with cirrhotic HBV-ACLF and 28 with ACLF with cirrhosis caused by non-HBV aetiologies (non-HBV-ACLF). The short-term (28/90 days) mortality of the patients with HBV-ACLF were significantly higher than those of the patients with non-HBV-ACLF. Total bilirubin (TB) ≥12 mg/dL and an international normalised ratio (INR) ≥1.5 was proposed as an additional diagnostic indicator of HBV-ACLF, and 19.3% of patients with an HBV aetiology were additionally diagnosed with ACLF. The new prognostic score (0.741×INR+0.523×HBV-SOFA+0.026×age+0.003×TB) for short-term mortality was superior to five other scores based on both discovery and external validation studies. Conclusions: Regardless of the presence of cirrhosis, patients with CHB, TB ≥12 mg/dL and INR ≥1.5 should be diagnosed with ACLF. The new criteria diagnosed nearly 20% more patients with an HBV aetiology with ACLF, thus increasing their opportunity to receive timely intensive management.